ANTUSIASME WARGA KELURAHAN NGAGEL REJO SURABAYA JELANG PILWALI 2020 - Maulana Firdaus Ferdiansyah; Liesmay Dwi Kurniawati; Ridho Akbar Prakoso; Adinda Ajeng Apriliana; Ike Dewi Purwanty; Agus Machfud Fauzi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2020)
Direct election 2020 in Surabaya are threatened with a decline in a politican participation. This condition is getting worse and has the potential to become a problem in the election of the mayor of Surabaya due to the expiration of two periods of Tri Rismaharini as the mayor of Surabaya. Placing the people of Surabaya in a difficult position to elect a new leader of Surabaya. Allegedly the departure of Tri Rismaharini will exacerbate the low enthusiasm of the community in the mayor election in 2020. The purpose of this study is to find out how the enthusiasm of the residents of the Ngagel Rejo urban village of Surabaya ahead of the 2020 pilwali. Using descriptive qualitative methods will thoroughly describe community enthusiasm. With Max Weber's theory of social action approaches and Fukuyama's concept of public trust. The results showed that the enthusiasm of the community was still very low, it was shown from the low curiosity, lack of knowledge about the figure of the candidate for mayor, pessimism, loss of trust in the government and politicians to the general election which he considered a regular 5 year routine and better used for work .